The Impact of Gamification on Purchase Behavior among the Smart Phone Users in Saudi Arabia Mediating Role of Purchase Intention and Moderating Role of Culture Dimensions (The Arab Journal of Administration, 2026)
The study aimed to measure the impact of marketing gamification on purchase intention and purchasing behavior among fashion sector customers using smartphones in Saudi Arabia, as well as the effect of purchase intention on purchasing behavior and the role of cultural dimensions (high-context vs. low-context communication- Internal vs. External Orientation) in this relationship. Using a descriptive analytical method and a simple random sample of 1,896 individuals, the findings revealed a statistically significant positive relationship between gamification and purchase intention, a direct positive effect of gamification on purchasing behavior, but a weak link between purchase intention and purchasing behavior, with cultural characteristics showing no moderating role.The study recommended focusing on gamification strategies, particularly tiered reward systems (Levels, Badges, Points) to encourage continuous engagement, reducing the gap between intention and behavior, leveraging cultural homogeneity to unify strategies in the Saudi market, employing attractive visual content, and integrating gamification elements with immediate motivational strategies to ensure consumers move from intention to action.